2017
DOI: 10.1007/s10461-017-1938-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the HIV Prevention and Care Continua in a Sample of Transgender Youth in the U.S.

Abstract: In the U.S., transgender and other gender minority (TG) youth are an at-risk group understudied in HIV prevention and treatment. This study sought to characterize the HIV prevention and care continua in a diverse sample of 181 sexually-active TG ages 16–24 years (mean age = 20.7 years; 76.8% trans feminine; 69.1% youth of color) recruited July–December 2015 in 14 U.S. cities. Overall, 30.9% reported living with HIV, of which 71.4% were on antiretroviral therapy (ART) and 55.0% were medication adherent; 65.6% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 69 publications
3
52
2
Order By: Relevance
“…The few studies we found indicated that transwomen have low HIV testing rates and low awareness of HIV status, low engagement and retention in HIV care, low medication adherence and low virologic suppression rates [4][5][6]. Suboptimal HIV engagement rates were found among transwomen from Brazil and US transgender youth [7,8]. African American transwomen were found to have even poorer reported viral suppression (24.5%) [9].…”
Section: Introductionmentioning
confidence: 83%
“…The few studies we found indicated that transwomen have low HIV testing rates and low awareness of HIV status, low engagement and retention in HIV care, low medication adherence and low virologic suppression rates [4][5][6]. Suboptimal HIV engagement rates were found among transwomen from Brazil and US transgender youth [7,8]. African American transwomen were found to have even poorer reported viral suppression (24.5%) [9].…”
Section: Introductionmentioning
confidence: 83%
“…2,4,8,9 Such stigma and discrimination are associated with poor mental health, substance abuse, violence, lack of familial and social support, homelessness, and unemployment-all of which compromise HIV care. 2,9 Additional barriers include TGNC people's limited access to and engagement in medical care, including HIV care, [10][11][12] and lack of knowledge and sensitivity among health care providers to treat TGNC people and address their needs. 11,13 Advances in HIV treatment, however, have created opportunities for people living with HIV (PLWH) to live longer and healthier lives.…”
Section: Introductionmentioning
confidence: 99%
“…A few smaller community samples (N = 22 to N = 181) report lower ART adherence rates spanning from 55% to 68% among predominantly transgender women samples, although measurement of adherence varies across studies. 12,[16][17][18][19][20] Community studies of transgender populations report adherence barriers such as negative health care experiences 16 and transphobia. 12 The National HIV/AIDS Strategy for the United States calls for improving health outcomes and decreasing health disparities among transgender people.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations